Mouse Thyroid Gland Changes in Aging: Implication of Galectin-3 and Sphingomyelinase. (11th December 2017) - Traina, Giovanna; Cataldi, Samuela; Siccu, Paola; Loreti, Elisabetta; Ferri, Ivana; Sidoni, Angelo; Codini, Michela; Gizzi, Chiara; Sichetti, Marzia; Ambesi-Impiombato, Francesco Saverio; Beccari, Tommaso; Curcio, Francesco; et al.
Abstract : Prevalence of thyroid dysfunction and its impact on cognition in older people has been demonstrated, but many points remain unclarified. In order to study the effect of aging on the thyroid gland, we compared the thyroid gland of very old mice with that of younger ones. We have first investigated the changes of thyroid microstructure and the possibility that molecules involved in thyroid function might be associated with structural changes. Results from this study indicate changes in the height of the thyrocytes and in the amplitude of interfollicular spaces, anomalous expression/localization of thyrotropin, thyrotropin receptor, and thyroglobulin aging. Thyrotropin and thyrotropin receptor are upregulated and are distributed inside the colloid while thyroglobulin fills the interfollicular spaces. In an approach aimed at defining the behavior of molecules that change in different physiopathological conditions of thyroid, such as galectin-3 and sphingomyelinase, we then wondered what was their behavior in the thyroid gland in aging. Importantly, in comparison with the thyroid of young animals, we have found a higher expression of galectin-3 and a delocalization of neutral sphingomyelinase in the thyroid of old animals. A possible relationship between galectin-3, neutral sphingomyelinase, and aging has been discussed.